Phosphate solubilization and plant growth promotion by two Pantoea strains isolated from the flowers of Hedychium coronarium L. - Prasad, Priyanka; Kalam, Sadaf; Sharma, Naveen Kumar; Podile, Appa Rao; Das, Subha Narayan (Frontiers in Agronomy, 2022)
Phosphorus (P) is an essential macronutrient for plants and is considered as one of the limiting nutrients to plants. The majority of P in the soil is found in the form of insoluble phosphate complexes, making the P unavailable for plants. In the present study, we report two highly efficient phosphate solubilizing bacteria isolated from the closed flower of Hedychium coronarium L., a medicinal plant commonly known as Gulbakawali. Based on morphological, biochemical, and molecular characterization, the two bacterial isolates were identified as genus Pantoea and designated as HCF6 and HCF9. Both these isolates efficiently solubilize tricalcium phosphate [Ca3(PO4)2] present in National Botanical Research Institute’s Phosphate (NBRIP) medium by releasing soluble phosphate up to 2000 μg ml-1 and also partially solubilize aluminium phosphate (AlPO4). HCF6 and HCF9 possess several plant growth promoting traits and were evaluated for plant growth promotion ability using sand as a growth medium. Wheat plants treated with the bacterial isolates had increased root and shoot length and plant dry mass and accumulated higher inorganic phosphate in the plant tissue suggesting their role in mobilizing soluble P from insoluble P-complexes. Overall, our findings suggest that both these Pantoea isolates (HCF6 and HCF9) represent promising candidates as bioinoculants.